Produktywność ziemi w rolnictwie polskim w latach 1960-1976 - Anszperger, Aleksander; Wiatrak, Andrzej Piotr (Wydział Prawa i Administracji UAM, 1978)
The contents of this study is a presentation of the land productivity determined by the value of total final production obtained from a hectare of arable land. The accomplished analysis informs, that sizes of final production and of land productivity grew in Polish agriculture in the years 1960 - 1976. The latter grew faster what resulted from a flow of land utilized in agriculture for non-agricultural purposes. The land productivity is the highest in individual economy, though we observed its growth in other sectors. The land producivity grew during the whole period, and particularly in the years 1971 - 1976. In that period the highest level of land productivity is achieved by Agricultural Work Co-operatives. The productivity growth proceeded irregularly in particular years, what was under considerable influence of economic policy of the state towards agriculture. It found expression first of all in the agricultural production structure and in the growth rates of its sectors. In the years 1960 - 1970 above all the growth of vegetable production was apparent, in the years 1971 - 1976 — the growth of animal production. Such development was shaped mainly by market parameters (f.ex. prices of agricultural products), which determined rentability of production of particular agricultural products. Differences in levels of the land productivity in particular sectors find expression in regional approach. These voivodeships, in which the state sector prevails, possess its lower level. In individual agriculture the land productivity is differentiated in dependence on a farm acreage. As the farm territory grows the land productivity diminishes, what is connected with production manners of peasants' economy. Small farms possess a great number of persons for a hectare of arable land and that leads to labour-consuming intensification. It confirms the diminishing share of animal production when a farm acreage grows.
The Land Productivity in Polish Agriculture in the Years 1960-1976